Block Trading and Information Revelation around Quarterly Earnings Announcements - Seppi, Duane J. (Review of Financial Studies, 1992)
The author investigate the empirical importance of information revelation in the pricing of block trades. In particular, he examine whether block prices are correlated with the unexpected part of firms' quarterly earnings. For his sample of block trades, information revelation does indeed appear to be a significant factor shortly before earnings announcements. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.